Predicting Financial Distress amongst Public Listed Companies in Malaysia - the Accuracy and Effectiveness of Altman’s Z-Score Model - Yee Leek, Hun Leek (AeU, 2015)
This paper focuses on predicting financial distress amongst Public Listed Companies (“PLCs”) in Malaysia using Altman’s Z-Score. Financial distress prediction models were pioneered by Beaver’s univariate test (1966) and Altman’s discriminant analysis (1968). Over the last four decades, prediction of financial distress has been of considerable interest to various users and stakeholders. In view of the significant impact of Asian financial crisis in 1997-1998, dotcom bubble that peaked in 2000, global financial crisis in 2007-2009, and the current world economic downturn, timely identification of financial distress could serve as an effective “early warning system” for signs of business collapses.